2005
DOI: 10.4049/jimmunol.175.5.2843
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Bacteria Differentially Regulated Endothelial Cytokine Release by MAPK-Dependent Histone Modification

Abstract: Epigenetic histone modifications contribute to the regulation of eukaryotic gene transcription. The role of epigenetic regulation in immunity to intracellular pathogens is poorly understood. We tested the hypothesis that epigenetic histone modifications influence cytokine expression by intracellular bacteria. Intracellular Listeria monocytogenes, but not noninvasive Listeria innocua, induced release of distinct CC and CXC chemokines, as well as Th1 and Th2 cytokines and growth factors by endothelial cells. Cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 66 publications
4
96
0
1
Order By: Relevance
“…Although consensus MAPK histone phosphorylation sites have not been described in vivo, MAPKs can activate histone-phosphorylating kinases (Cheung et al, 2000;Zhong et al, 2001). For example, ERK1/2 and p38a, -b can provoke changes in chromatin structure (Li et al, 2001;Illi et al, 2005;Schmeck et al, 2005) most likely owing to the activation of downstream kinases such as MSK1/2 (Saccani et al, 2002;Soloaga et al, 2003;Lee et al, 2006a;Vicent et al, 2006) or RSK2 (Cheung et al, 2000) that phosphorylate the N-terminal tail of histones. A surprising recent finding is that MAPKs bind to specific actively transcribed genes, as documented in yeast (Pokholok et al, 2006), reinforcing the idea that MAPKs participate actively in chromatin remodeling, perhaps explaining the observation that MAPKs such as p38a and ERK1/2 bind cellular DNA as judged by the use of chromatin immunoprecipitation assays in mammalian cells (Simone et al, 2004;Vicent et al, 2006).…”
Section: Signal Integration In the Nucleus: Spatiotemporal Regulationmentioning
confidence: 99%
“…Although consensus MAPK histone phosphorylation sites have not been described in vivo, MAPKs can activate histone-phosphorylating kinases (Cheung et al, 2000;Zhong et al, 2001). For example, ERK1/2 and p38a, -b can provoke changes in chromatin structure (Li et al, 2001;Illi et al, 2005;Schmeck et al, 2005) most likely owing to the activation of downstream kinases such as MSK1/2 (Saccani et al, 2002;Soloaga et al, 2003;Lee et al, 2006a;Vicent et al, 2006) or RSK2 (Cheung et al, 2000) that phosphorylate the N-terminal tail of histones. A surprising recent finding is that MAPKs bind to specific actively transcribed genes, as documented in yeast (Pokholok et al, 2006), reinforcing the idea that MAPKs participate actively in chromatin remodeling, perhaps explaining the observation that MAPKs such as p38a and ERK1/2 bind cellular DNA as judged by the use of chromatin immunoprecipitation assays in mammalian cells (Simone et al, 2004;Vicent et al, 2006).…”
Section: Signal Integration In the Nucleus: Spatiotemporal Regulationmentioning
confidence: 99%
“…4,5 Another study reported a drastic decrease of global pH3Ser10 upon L. monocytogenes infection. 6 This decrease was attributed to the bacterium's extracellular presence, and mediated by the cytolysin listeriolysin: a global decrease of pH3Ser10 was dependent on membrane binding of listeriolysin but not on its pore-forming activity.…”
Section: Introductionmentioning
confidence: 99%
“…33 Lm modifies host gene expression via 2 virulence factors, LntA and LLO. [20][21][22]34 LLO modulates host transcription from the extracellular milieu and is degraded once Lm escapes the vacuole, being unlikely to modify host histones from the cytoplasm. 20 Our data do not support a crucial role for LLO or any other bacterial secreted proteins acting from the extracellular milieu.…”
Section: Discussionmentioning
confidence: 99%
“…19 The interplay between Lm and the host cell cycle is understudied. Albeit Lm remains mostly cytosolic, it interferes with histone modifications 20,21 and chromatin-regulatory factors 22 to modulate host gene expression.…”
Section: Introductionmentioning
confidence: 99%